The Domino Effect of Cross-Cultural Miscommunication in Multinational Manufacturing and Service Organisations in the Netherlands - Tetteh, Eugenia (Digital Repository of Theses - SSBM Geneva, 2025)
A lot of studies have been devoted to cross-cultural communication because researchers claim that multinational teams face a lot of challenges due to their differences in culture. Some researchers also called for research to be conducted on individual situations that occurred in the working relationships of multinational people. Therefore, this research aimed to gain knowledge and insight into how cross-cultural miscommunication influenced multinational teams, whilst looking into how their differences affected their working relationships and the effect this had on the company. Besides, the literature demonstrated that cultural differences among employees led to misrepresentations, mistrust, anger and confusion, among others. The qualitative research method was applied by the researcher, through semi-structured interviews, to gather the data for the research. Mediums for communicating and the interviews were through MS Teams, WhatsApp, and email. 20 research participants from multinational service and manufacturing organisations were interviewed, comprising 7 managers (2 were company directors), 1 supervisor, and 12 general employees. Additionally, I used the Thematic analysis of Braun and Clark (2006) to analyse the data. The findings of the research established that cultural values, traditions, communication styles, and corporate cultural practices were remote causes of cultural miscommunication in teams, leading to misrepresentations and collaboration challenges, which had organisational consequences. Also, verbal and non-verbal communication and power distance had some influence on the leader/subordinate miscommunication consequences. This research contributes to ongoing debates and literature on the effects of cross-cultural miscommunication and closes the gap on the ripple effects of multinational cultural miscommunication issues. Strategies that management could apply to reduce cross-cultural miscommunication include cross-cultural training, creating a common business language, feedback frameworks to tackle cross-cultural issues, and organising annual cultural team-building and awareness fun events. The study’s limitations included non-generalizability and time-consuming factors resulting from the use of a qualitative method. It was concluded that cross-cultural miscommunication has a lot of consequences, which affect the working relations of employees, their collaboration in teams, and could eventually affect their output, leading to possible turnover, demotivated employees, and lower revenue for the company. Based on the literature gaps and findings, it is recommended that future studies be conducted on how the combination of certain cultures in teams could affect their productivity and efficiency, and how the cultural background of teachers and lecturers impacts students’ scores in exams and assignments.